Pemanfaatan Media Online Oleh Masjid Jogokariyan Yogyakarta Dalam Membangun Komunikasi Dengan Aktivis Dakwah Tahun 2017 - Muhammad Afnan Banu Aji; Tri Hastuti Nur Rochimah (UMSU, 2019)
This study analyzed of management online media conducted by Yogyakarta Jogokariyan Mosque for building and fostering a communication with da'wah activists in 2017. The research method used was descriptive qualitative, and data collection techniques through interviews and document data. The results of this research that management of online media in Yogyakarta Jogokariyan Mosque does not plan regularly and systematically but is more flexible and incidental. The platform media that is most widely used to promote and build communication networks with da'wah activists is Facebook and Instagram by basing it on the intended target audience and effectiveness level. To evaluate how to use the online media of the Jogokariyan Mosque, they carried out media monitoring on the response of the audience both who followed, like, share and commented.